Current and emerging therapies in premature ejaculation: Where we are coming from, where we are going. (5th October 2016) - Martin, Christopher; Nolen, Hunter; Podolnick, Jason; Wang, Run
Abstract: Premature ejaculation is the most common form of sexual dysfunction among men. The pathophysiology of premature ejaculation appears to be multifactorial, implicating the need for multimodal therapeutic regimens to successfully treat premature ejaculation. Multiple treatment regimens have been shown to be effective in extending the time between penetration and ejaculation. These treatment modalities include everything from behavioral modifications and medications to diet alterations and major surgery. The goal of the present article was to review the commonly used treatment regimens used in the treatment of premature ejaculation, as well as to introduce and discuss the newest treatment routines under study for the treatment of premature ejaculation.